Microsociología de la prostitución femenina en el espacio público de la ciudad de Buenos Aires - Nuñez, Lucia (2018)
The present work aims to analyze, from a microsociological approach, the interactions of migrant women and men (clients/prostitute hirers) in the exercise of prostitution in public spaces of the Ciudad Autónoma de Buenos Aires. Starting from the premise that the observation, description and analysis of these specific interactions make it possible to account for the ways in which hierarchies are built around female corporalities in the sex market, for example, through ethnic-racial stereotypes, anchored in the national dimension involved in the development of this practice, among others. For this, part of the field work carried out by the undersigned in recent years will be appealed, focusing on the ethnographic observations made in two historical sites of prostitution in the public space of the city. The choice of these places refers to the fact that they present a specific spatial organization mode (concentration/dispersion), while they present a population exercising this practice differentiated in sex-gender and national terms.